Evaluating Outcomes of Percutaneous Nephrolithotomy Versus Flexible Ureteroscopy for Renal Calculi: A Retrospective Observational Study in Misrata, Libya (Razi Medical Journal, 2025)
Nephrolithiasis is a significant and growing global health burden with rising prevalence and recurrence rates. Management of renal calculi sized 1–2.5 cm remains debated, with percutaneous nephrolithotomy (PCNL) and flexible ureteroscopy (fURS) being the most commonly used minimally invasive approaches. Evidence comparing both procedures in the Libyan setting is limited. This study aimed to compare the efficacy and safety outcomes of PCNL and fURS in patients with renal stones sized 1–2.5 cm, with a focus on perioperative characteristics, renal function, stone-free rate (SFR), and postoperative complications. A retrospective, multicenter observational study was conducted at two hospitals in Misrata, Libya, between January 2020 and December 2024. A total of twenty patients were included, equally divided between PCNL (n=10) and fURS (n=10). Demographic, clinical, and perioperative variables were collected from patient records. Outcomes assessed included renal function, SFR, drainage method, complications, blood transfusion, and need for secondary intervention. The mean age was 49.2 ± 12.2 years, with male predominance 55%. Solitary stones (75%) and renal pelvis location (60%) were the most common. The fURS group had a significantly higher prevalence of patients with a history of renal stones (70% vs. 20%, p=0.025) and previous extracorporeal shockwave lithotripsy (ESWL) (60% vs. 10%, p=0.019). Postoperatively, renal function abnormalities occurred only in fURS cases (p = 0.025). Drainage methods differed significantly, with fURS exclusively using double J stents and PCNL with a nephrostomy tube (p = 0.001). No statistically significant differences were found in SFR, operation time, hospital stay, fever, or transfusion rates between the two groups. Both PCNL and fURS are effective and safe for managing 1–2.5 cm renal stones, with comparable SFRs and complication rates. fURS were more commonly employed after failed conservative management and were associated with transient renal function impairment, whereas PCNL required nephrostomy drainage. Larger, prospective studies are needed to confirm these findings and guide practice in Libya.
Keywords: Percutaneous Nephrolithotomy, Flexible Ureteroscopy, Renal Calculi, Kidney Stones, Libya